Evaluation and accreditation of the postdegree quality in the specialties of Internal Medicine and Dermatology in Santiago de Cuba - Idalberto Senú Gonzàlez; Nilia Victoria Escobar Yéndez; Yamila Valiente Hernández; Lisset Bandera Sosa; Maritza Berenguer Guarnaluces (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: The training management and the improvement of the academic postdegree programs are urgency necessities for the permanent training of the professionals in the Cuban universities of medical sciences. Objective: To socialize the systematized experiences in the processes of quality management of the postdegree programs in two medical specialties. Methods: A diagnosis and an external evaluation of the post degree academic programs in the specialties of Internal Medicine and Dermatology were carried out in the Medical Sciences University in Santiago de Cuba, in the months of May and September, 2019 respectively, where the observation of the different activities of each program was considered through the development of the six established variables for it, which contributed to reveal the main strengths and weaknesses of these study programs. Results: The integral analysis of the programs evidenced, during the process of external evaluation, the fulfillment of the established standards in the quality pattern, reason why it was unanimously decided, in the 49 Session Agreement of the National Accreditation Meeting from October, 2019, to grant them the accreditation higher category of Excellency Program. Conclusions: It could be demonstrated that in the training management of both specialties, as academic figures of postdegree,  have been revealed with assertiveness the pertinent impacts for the National System of Public Health.